Textile antenna for RF energy harvesting fully embedded in clothing - Loss, Caroline (2019)
In the context of Wireless Body Sensor Networks for healthcare and pervasive applications, textile antennas allow an ubiquitous monitoring, communication, energy harvesting and storage. This paper presents a smart coat with a dual-band textile antenna for Radio Frequency (RF) energy harvesting, operating at GSM 900 and DSC 1800 bands, which is fully embedded in the garment. Results obtained before and after the integration of the antenna into the garment are compared. The gain obtained in the simulation is about 1.8 dBi and 2.06 dBi, with radiation efficiency of 82% and 77,6% for the lowest and highest operating frequency bands, respectively.